Layperson-Led vs Professional-Led Behavioral Interventions for Weight Loss in Pediatric Obesity: A Systematic Review and Meta-analysis - McGavock, Jonathan (JAMA Netw Open, 2020)
IMPORTANCE: The appropriate approach for weight loss among children and adolescents with overweight and obesity remains unclear. OBJECTIVE: To evaluate the difference in the treatment outcomes associated with behavioral weight loss interventions led by laypersons and professionals in comparison with unsupervised control arms among children and adolescents with overweight and obesity. DATA SOURCES: For this systematic review and meta-analysis, the Medical Literature Analysis and Retrieval System Online (MEDLINE), Embase, the Cochrane Library, and Cumulative Index of Nursing and Allied Health Literature (CINAHL) databases were searched from January 1, 1996, to June 1, 2019. STUDY SELECTION: Included in this study were randomized clinical trials (RCTs) of behavioral interventions lasting at least 12 weeks for children and adolescents (aged 5-18 years) with overweight and obesity. Exclusion criteria included non-RCT studies, interventions lasting less than 12 weeks, adult enrollment, participants with other medical diagnoses, pharmacological treatment use, and articles not written in English. Two of 6 reviewers independently screened all citations. Of 25 586 citations, after duplicate removal, 78 RCTs (5780 participants) met eligibility criteria. DATA EXTRACTION AND SYNTHESIS: A bayesian framework and Markov chain Monte Carlo simulation methods were used to combine direct and indirect associations. Random-effects and fixed-effect network meta-analysis models were used with the preferred model chosen by comparing the deviance information criteria. This study was registered with the International Prospective Register of Systematic Reviews (PROSPERO) and followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guideline. MAIN OUTCOMES AND MEASURES: The immediate and sustained changes in weight and body mass index (BMI) standardized mean difference (SMD) were primary outcomes planned before data collection began, whereas waist circumference and percent body fat were secondary outcomes. The hypothesis being tested was formulated before the data collection. RESULTS: Of 25 586 citations retrieved, we included 78 RCTs (5780 participants), with a follow-up of 12 to 104 weeks. Compared with the control condition, random-effects models revealed that professional-led weight loss interventions were associated with reductions in weight (mean difference [MD], −1.60 kg [95% CI, −2.30 to −0.99 kg]; 68 trials; P < .001) and BMI (SMD, −0.30 [95% CI, −0.39 to −0.20]; 59 trials; P < .001) that were not sustained long term (weight MD, −1.02 kg [95% CI, −2.20 to 0.34 kg]; 21 trials; P = .06; BMI SMD, −0.12 [95% CI, −0.46 to 0.21]; 20 trials; P < .001). There was no association between layperson-led interventions and weight loss in the short-term (MD, −1.40 kg [95% CI, −3.00 to 0.26 kg]; 5 trials; P = .05) or long-term (MD, −0.98 kg [95% CI, −3.60 to 1.80 kg]; 1 trial; P = .23) compared with standard care. No difference was found in head-to-head trials (professional vs layperson MD, −0.25 kg [95% CI −1.90 to 1.30 kg]; 5 trials; P = .38). CONCLUSIONS AND RELEVANCE: This systematic review and meta-analysis found that professional-led weight loss interventions were associated with short-term but not sustained weight reduction among children and adolescents with overweight or obesity, and the evidence for layperson-led approaches was insufficient to draw firm conclusions.